Implementasi Aplikasi Rapor UTS Online Kurikulum Merdeka Di MTS Tarbiyatul Wathon Gresik - Lisdiyanto, Angga; ., Winarti; Andhyka, Awang; Mu'min, Syahri; Saputro, Arief; Nugroho, Rizky Aditya; Mufliq, Achmad; Abdillah, Ikhwan; Djanah, Miftahul; Lutfiyah, Nanik; Siswanto, Markhaban (CV. ITTC INDONESIA, 2024)
After the Covid-19 pandemic, Indonesia's education system transformed with the introduction of the